2014
DOI: 10.1007/s13277-014-2522-8
|View full text |Cite
|
Sign up to set email alerts
|

PCAF-mediated Akt1 acetylation enhances the proliferation of human glioblastoma cells

Abstract: Glioblastoma is the most aggressive malignant primary brain tumor in humans. The activation of PI3K/Akt1 signaling pathway is involved in the proliferation of glioblastoma; however, the underlying mechanism of Akt1 activation during the development of glioblastoma remains largely unclear. Recently, the modification of molecular molecules at protein level such as acetylation has been shown to be related to the function of these molecules. Thus, in our present studies, the acetylation of Akt1 molecule and its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Similar to Elp3, PCAF has been shown to acetylate non-histones proteins such as β-catenin (Ge et al, 2009), Akt1 (Zhang et al, 2015), Stat3 (Cai et al, 2014) and lin28 (Wang et al, 2014). It would be interesting to test whether PCAF is also involved in the regulation of Cx43 acetylation in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Elp3, PCAF has been shown to acetylate non-histones proteins such as β-catenin (Ge et al, 2009), Akt1 (Zhang et al, 2015), Stat3 (Cai et al, 2014) and lin28 (Wang et al, 2014). It would be interesting to test whether PCAF is also involved in the regulation of Cx43 acetylation in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the regulation of Akt1 phosphorylation remains elusive. Given that Akt1 is able to undergo acetylation, which is an essential regulatory mehcanism required for Akt phosphorylation and subsequent activation (27), Akt1 acetylation was further measured in NPC cells stimulated by IL-17A. The results of the present study demonstrated that the level of Akt1 acetylation was markedly elevated in human NPC cells treated with IL-17A compared with the isotype IgG treated control group.…”
Section: Discussionmentioning
confidence: 62%
“…2A). It has been reported that the modification of protein acetylation is an important post-transcriptional regulation that may promote Akt1 phosphorylation (27). Therefore, the effect of IL-17A stimulation on Akt1 acetylation was studied in C666-1 cells subsequently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in medulloblastoma and glioblastoma cells, Pcaf interacts with Gli1 to promote hyperactive Hedgehog-Gli1 signaling and high cellular proliferation 227 . Notably, Pcaf mediates many of its oncogenic functions via acetylation of non-histone targets including Ezh2 228 , Akt1 229 , Acly ( A TP- c itrate l yase) 230 , and β-catenin 231 . Pcaf-mediated acetylation of Ezh2, Acly and β-catenin leads to improved protein stability and tumor-promoting characteristics in lung 228; 230 and colon cancer 224 , respectively.…”
Section: Tumor Initiation and Progressionmentioning
confidence: 99%